Thinking digital: DOI usage in Spanish journals, a subject still pending - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2013)
This note aims to highlight the expanded use of the Digital Object Identifier by Spanish journals, which despite its implementation is still a pending course. The doi is a basic tool for digital document control, allowing secure permanent citations between documents. Therefore it should be considered a quality publishing factor for electronic journals. The doi system has been adopted as ISO 26324:2012, and more than 200 Spanish journals are applying it via the CrossRef consortium. Its extension affects bibliographic citation practices and several documentation areas should be interested in it.
Keywords: Digital object identifier; DOI; CrossRef; Academic journals; Permalink; Editorial quality.